2018
DOI: 10.1155/2018/1246069
|View full text |Cite
|
Sign up to set email alerts
|

Altered Redox Homeostasis in Branched‐Chain Amino Acid Disorders, Organic Acidurias, and Homocystinuria

Abstract: Inborn errors of metabolism (IEMs) are a group of monogenic disorders characterized by dysregulation of the metabolic networks that underlie development and homeostasis. Emerging evidence points to oxidative stress and mitochondrial dysfunction as major contributors to the multiorgan alterations observed in several IEMs. The accumulation of toxic metabolites in organic acidurias, respiratory chain, and fatty acid oxidation disorders inhibits mitochondrial enzymes and processes resulting in elevated levels of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 175 publications
(216 reference statements)
1
21
0
Order By: Relevance
“…), the hydroxyl radical (●OH), and hydrogen peroxide (H 2 O 2 ). The autoxidation of Hcy can generate ●OH and H 2 O 2 [ 108 ]. However, the role of autoxidation in Hcy-induced cell oxidative stress has been questioned, due to the fact that other thiols—such as cysteine—are present at much higher concentrations than Hcy, which can also undergo autoxidation and are not associated with impaired redox balance [ 109 ].…”
Section: Mechanisms Induced By Hhcy Associated With Endothelial Dymentioning
confidence: 99%
See 1 more Smart Citation
“…), the hydroxyl radical (●OH), and hydrogen peroxide (H 2 O 2 ). The autoxidation of Hcy can generate ●OH and H 2 O 2 [ 108 ]. However, the role of autoxidation in Hcy-induced cell oxidative stress has been questioned, due to the fact that other thiols—such as cysteine—are present at much higher concentrations than Hcy, which can also undergo autoxidation and are not associated with impaired redox balance [ 109 ].…”
Section: Mechanisms Induced By Hhcy Associated With Endothelial Dymentioning
confidence: 99%
“…High Hcy levels have been previously associated with decreased glutathione [ 122 ], a key cellular antioxidant, in cardiac patients, as well as with a reduction in vitamins B12 and E in HHcy patients [ 107 ]. GPx (GPx-1 and GPx-2), SOD (SOD1 and SOD2), and thioredoxin expression were also found reduced in hyperhomocysteinemic mice and endothelial cells [ 107 , 108 , 120 , 123 ]. Moreover, a recent study including hypertensive hyperhomocysteinemic patients showed that patients with high tHcy levels had lower plasma SOD and catalase when compared to patients with normal plasma Hcy [ 119 ].…”
Section: Mechanisms Induced By Hhcy Associated With Endothelial Dymentioning
confidence: 99%
“…The cellular pathway in MMA by which cobalamin (OH-Cbl) is processed to AdoCbl and methylcobalamin (MeCbl) is depicted in Figure 1. The cobalamin-processing enzymes have been indicated to be causative factors (Obeid et al, 2015; Richard et al, 2018). MMA can be classified into two common types: isolated MMA and combined MMA and homocysteinemia, which are caused by deficiency in the MUT or MMACHC gene, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…D-methylmalonyl-CoA is subsequently racemized by methylmalonyl-CoA epimerase (methylmalonyl-CoA racemase) to L-methylmalonyl-CoA. Disorders of MMA includes a heterogeneous group of disorders caused by several different deficiencies: (1) in methylmalonyl-CoA epimerase; (2) in L-methylmalonyl-CoA mutase (MCM), which isomerizes L-methylmalonyl-CoA to succinyl-CoA; (3) defects in cobalamin absorption or intracellular trafficking; (4) intracellular defects involving the distal steps of the cobalamin processing pathway (cblA, cblB, cblD2) impacting solely on the synthesis of the co-factor adenosylcobalamin essential for MCM activity, resulting in isolated MMA; (5) intracellular defects involving the proximal steps in the cobalamin processing pathway (cblC, cblD, cblE, cblF, cblG, cblJ) impacting on the synthesis of both methylcobalamin, the co-factor for methionine synthase, and adenosylcobalamin, the co-factor for MCM activity, resulting in combined MMA and homocystinuria ( 28 , 30 ).…”
Section: Systemic Organic Acidemiasmentioning
confidence: 99%
“…Since oxidative phosphorylation is inhibited in PA, a redox imbalance and increased oxidative stress are predicted for PA hearts. Indeed, oxidative stress has been implicated as an important mechanism involved in the pathophysiology of PA ( 30 ), which is likely to be involved in PA-induced cardiac dysfunction. Increased intracellular hydrogen peroxide has been detected in PA patient fibroblasts, indicating increased oxidative stress is apparent in PA ( 130 ).…”
Section: Cardiac Dysfunction In Propionic Acidemiamentioning
confidence: 99%